Chasing literacy : reading and writing in an age of acceleration - Keller, Daniel, 1977- (Logan : Utah State University Press, 2014)
"Arguing that composition should renew its interest in reading pedagogy and research, Chasing Literacy offers writing instructors and literacy scholars a framework for understanding and responding to the challenges posed by the proliferation of interactive and multimodal communication technologies in the twenty-first century.Employing case-study research of student reading practices, Keller explores reading-writing connections in new media contexts. He identifies a culture of acceleration--a gathering of social, educational, economic, and technological forces that reinforce the values of speed, efficiency, and change--and challenges educators to balance new "faster" literacies with traditional "slower" literacies. In addition, Keller details four significant features of contemporary literacy that emerged from his research: accumulation and curricular choices; literacy perceptions; speeds of rhetoric; and speeds of reading.Chasing Literacy outlines a new reading pedagogy that will help students gain versatile, dexterous approaches to both reading and writing and makes a significant contribution to this emerging area of interest in composition theory and practice"--
"Arguing that composition should renew its interest in reading pedagogy and research, Chasing Literacy offers writing instructors and literacy scholars a framework for understanding and responding to the challenges posed by the proliferation of interactive and multimodal communication technologies in the twenty-first century. Employing case-study research of student reading practices, Keller explores reading-writing connections in new media contexts. He identifies a culture of acceleration--a gathering of social, educational, economic, and technological forces that reinforce the values of speed, efficiency, and change--and challenges educators to balance new "faster" literacies with traditional "slower" literacies. In addition, Keller details four significant features of contemporary literacy that emerged from his research: accumulation and curricular choices; literacy perceptions; speeds of rhetoric; and speeds of reading. Chasing Literacy outlines a new reading pedagogy that will help students gain versatile, dexterous approaches to both reading and writing and makes a significant contribution to this emerging area of interest in composition theory and practice"--
Locating reading in composition studies -- Perceptions of literacy -- Reading in a culture of acceleration -- Directing attention: multitasking, foraging, oscillating -- Reading-writing connections.
Includes bibliographical references and index.
Keywords: Reading; Information technology; Literacy